THE ROLE OF VILLAGE GOVERNMENT IN IMPROVING WELFARE IN THE WAIRBLELER VILLAGE FISHERMAN COMMUNITY - Danar Aswim; Oviyanti Dua Simpi (Journal Civics And Social Studies, 2022)
The purpose of this study is to find out more about the role of the Village Government in improving the welfare of the fishing community and the inhibiting factors of the Village Government in improving the welfare of the fishing community in Wairbleler Village, Waigete District, Sikka Regency. This study uses a qualitative approach method. The data sources used are primary data sources and secondary data sources. The informants involved in this research are the village government and fishing communities. Data collection techniques used include observation techniques, interviews and documentation. Data analysis techniques consist of data reduction (data reduction), data display (data presentation) and conclusion drawing/verification. Based on the results of the research that the Wairbleler Village Government has carried out its role by providing motivation in the form of procuring FADs, providing fishing gear facilities and providing training, the Wairbleler Village Government has carried out its role well to meet all the needs and problems of the fishing community and for various inhibiting factors the welfare of the fishing community in the form of a budget, late distribution, uneven distribution of assistance. This study suggests that the Wairbleler Village Government together with the Sikka District Fisheries Service provide facilities and pay more serious attention so that there is an even distribution of assistance so that it can increase the capture power of fishery products.